2005
DOI: 10.1111/j.1460-9568.2005.04268.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐vasopressin and vasointestinal polypeptide rhythms in the suprachiasmatic nucleus of the mouse lemur reveal aging‐related alterations of circadian pacemaker neurons in a non‐human primate

Abstract: The suprachiasmatic nucleus (SCN) of the hypothalamus, the mammalian circadian pacemaker, is entrained by external cues and especially by photic information. Light is transmitted primarily via the retinohypothalamic tract, which terminates in the ventral part (or core) of the SCN, where vasoactive intestinal polypeptide (VIP)-containing neurons are located. VIP cells are mainly intrinsic and project to the dorsal part (or shell) of the SCN, where neurons containing arginine-vasopressin (AVP) reside. As aging l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 64 publications
(86 reference statements)
2
42
0
2
Order By: Relevance
“…The flattening of the daily rhythm in vasopressin abundance was already observed in subjects >50 years of age (160). Similar decreases in the expression of vasopressin in the SCN were also noted in aging experimental animals (161163). Harper et al (164) very elegantly demonstrated that the loss of SCN vasopressin-expressing neurons in the human postmortem brain significantly correlated with an increased deterioration of activity rhythms before death.…”
Section: A Disorganized Clocksupporting
confidence: 71%
“…The flattening of the daily rhythm in vasopressin abundance was already observed in subjects >50 years of age (160). Similar decreases in the expression of vasopressin in the SCN were also noted in aging experimental animals (161163). Harper et al (164) very elegantly demonstrated that the loss of SCN vasopressin-expressing neurons in the human postmortem brain significantly correlated with an increased deterioration of activity rhythms before death.…”
Section: A Disorganized Clocksupporting
confidence: 71%
“…14, 64, 106, 107, and Figure 3). A similar reduction in AVP and VIP expression has been observed in aged rodents (108,109), whereas in mouse lemurs, a nonhuman primate, the peak of rhythmic AVP and VIP expression in the SCN is shifted, not suppressed, in aged animals compared with younger adults (110).…”
Section: Sensitivity To Zeitgebersmentioning
confidence: 64%
“…AVP (arginine vasopressine neurons in the dorsomedial region of the SCN) and VIP (vasoactive intestinal polypeptide, in the ventrolatreal region of SNC), constitute the main output pathway of the SCN to the rest of the brain. Several animal and human studies reported an age-related shift [70] and decrease in the rhythmic synthesis, oscillation and release of these neuropeptides [25], [71] along with a decrease in the number of AVP-expressing neurons in the SCN [72]. Post-mortem analyzed of human brains, also show a flattened diurnal oscillation of AVP expression in older subjects compared to young [73].…”
Section: Discussionmentioning
confidence: 98%